Estrategias motivacionales en la mejora de la comprensión de textos escritos en inglés en estudiantes de tercer grado de secundaria en la Institución Educativa Petronila Perea de Ferrando de Punchana 2023 - Ortiz Pacaya, Anggela Shumey (2024)
The main objective of the study was to evaluate the effect of motivational strategies to improve the comprehension of written texts in English in third grade secondary students at Petronila Perea de Ferrando school in Punchana 2023. The type of study used was evaluative with designs: field study, contemporary transectional, univariate and quasi-experimental. The population for this study was 105 students and the sample consisted of 37 students, 21 in the experimental group and 16 in the control group. To obtain data, the pre and post comprehension test was used, which was validated by three experts in the area, giving 85% of its validity to be applied to the students; in the pilot test it resulted with a confidence of 80%. The results showed that the students in the experimental group achieved a significantly higher mean than the control group in the variable comprehension of written texts in English (12.25 > 8.14 on a vigesimal scale). Similarly, for the results obtained for the dimensions, obtaining information (13.71 > 7.87); inference and interpretation (9.18 > 7.69); evaluation of form, content and context (13.05 > 8.82). Therefore, it is statistically concluded that motivational strategies significantly improved the comprehension of written texts in English in third grade students, because the p value was 0.000 < ɑ=0.05.